PREVALENCE OF FASCIOLIOSIS IN BUFFALOES AND COMPARATIVE EFFICACY OF ENDOACTIVEN AND NITROXYNIL AGAINST FASCIOLIOSIS - A. Z. Durrani; M. S. Khan; N. Kamal (Journal of Animal and Plant Sciences, 2007)
The prevalence of fascioliosis in 12 different villages of union council Jia Bagga, District Lahore was studied. The comparative efficacy of two flukicidal drugs namely Nitroxynil (Trodax, 34%) and Endoectiven (Closantal) was evaluated. For this purpose 200 buffaloes were randomly selected on the basis of clinical signs like foul smelling, watery diarrhoea, swelling on the brisket, bottle jaw, anorexia and hypothermia with abrupt decrease in milk yield. Among these, 60 animals were confirmed positive for Fasciola with floatation technique. These animals were divided into three groups namely, A, B and C. Group A remained as untreated (control). Group B was medicated with Nitroxynil, while group C was medicated with Endoectiven. Eggs per gram counts of feaces were made with the help of modified Mc. Master technique on zero day pre-medication and on 7th day post medication. The results showed 30% prevalence of F .hepatica infection. The percentage efficacy for Nitroxynil was 93.88, while for Endoectiven it was 91.91%. Side effect of local swelling at the site of injection which lasted for about one month was recorded for Endoectiven while for Nitroxynil, no side effects were recorded.
Keywords: Fascioliosis; Nitroxynil; Endoectiven.